Single-cell transcriptomics reveals a novel mechanism of RDH16 regulating immune infiltration in hepatocellular carcinoma - Zhang, Zhenzhen; Fan, Rui; Ma, Jing; Li, Dehui; Jiang, Yan; Liu, Fahui; Gong, Qiming (Frontiers in Immunology, 2026)
IntroductionHepatocellular carcinoma (HCC) exhibits pronounced intratumoral heterogeneity and a complex immune microenvironment, which together limit therapeutic efficacy. Identifying actionable biomarkers and mechanisms of immune modulation remains critical for improving patient outcomes.MethodWe integrated single-cell RNA sequencing data with bulk transcriptomic datasets to comprehensively characterize tumor cell heterogeneity and immune landscape features in HCC. Associations between RDH16 expression and clinicopathological characteristics were evaluated, and in vitro functional assays were conducted. Mendelian randomization analyses were performed to assess causal relationships.ResultsRDH16 expression was significantly reduced in HCC tissues compared with non-tumor liver tissues and was associated with vascular invasion, elevated alpha-fetoprotein levels, poor tumor differentiation, and advanced T stage. Higher RDH16 expression was consistently associated with improved overall prognosis. Functional assays indicated that RDH16 did not directly affect tumor cell proliferation, migration, or invasion. Notably, RDH16 expression was inversely correlated with infiltration of CD163⁺ M2 macrophages, suggesting a potential immunomodulatory role in the tumor microenvironment. Mendelian randomization analyses further supported a protective effect of higher RDH16 expression against HCC risk.DiscussionThese findings identify RDH16 as an immune-modulating biomarker in HCC, highlighting its potential role in shaping the tumor immune microenvironment and suggesting new avenues for personalized immunotherapeutic strategies.